2019
DOI: 10.1093/rb/rbz011
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of 3D printed polycaprolactone scaffolds with angle-ply architecture for annulus fibrosus tissue engineering

Abstract: Tissue engineering of the annulus fibrosus (AF) is currently being investigated as a treatment for intervertebral disc degeneration, a condition frequently associated with low back pain. The objective of this work was to use 3D printing to generate a novel scaffold for AF repair that mimics the structural and biomechanical properties of the native tissue. Multi-layer scaffolds were fabricated by depositing polycaprolactone struts in opposing angular orientations, replicating the angle-ply arrangement of the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 68 publications
1
28
0
Order By: Relevance
“…Without the encumbrances such as complexity of the production process, uncertainty of mechanism involving drug delivery, and disturbance of tendon regeneration, the inherent plain structure is one of Recently, oriented materials and their applications in orthopedic tissue engineering have been studied intensively, including peritoneal adhesion, 16 cartilage degeneration, 15 peripheral nerve defect, 13 annulus fibrosus implant, 12 and rotator cuff tendon defect. 14 However, there is still no application in the field of biomaterials for tendon adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Without the encumbrances such as complexity of the production process, uncertainty of mechanism involving drug delivery, and disturbance of tendon regeneration, the inherent plain structure is one of Recently, oriented materials and their applications in orthopedic tissue engineering have been studied intensively, including peritoneal adhesion, 16 cartilage degeneration, 15 peripheral nerve defect, 13 annulus fibrosus implant, 12 and rotator cuff tendon defect. 14 However, there is still no application in the field of biomaterials for tendon adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…As Shh and Bra are expressed only by the NP cells and not by AF cells, 32,33,41 these markers were used to identify NP cell contamination in the AF cell preparations. Tnmd is a specific molecular marker of the AF cells and is not expressed by NP cells in the intervertebral disc 34 . Hence, expression analysis of Tnmd was used to validate the absence of AF cells in the NP cell preparations.…”
Section: Validation Of the Methodsmentioning
confidence: 99%
“…The following protocol may be used to microdissect and isolate each component of the disc from E16.5 to all ages during the postnatal stage in mice. The purity of the NP and AF samples was validated by analyzing the expression of specific molecular markers using Brachyury ( Bra , Tbxt , or T , 32 ) and sonic hedgehog ( Shh , 33 ) for NP cells, and tenomodulin ( Tnmd , 34 ) for AF cells. While this methods paper describes cell isolation from the lumbar disc, as degeneration and chronic low back pain is highly prevalent at this level of spine in mice, 26,35 we currently use the same methodology for microdissection and isolation of equally pure populations of NP and AF cells from the cervical, thoracic, and caudal discs of postnatal mice of all ages.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional printing precisely fabricates the scaffold structure. To generate a scaffold with angle-ply architecture similar to natural AF, Christiani et al (2019) printed laminar constructs comprised of polycaprolactone (PCL) struts oriented at alternating angles of ±30°. The mechanical characterization results showed that the mechanical properties of the scaffolds were similar to native AF tissue.…”
Section: Tissue Engineering Strategiesmentioning
confidence: 99%